2003
DOI: 10.1111/j.1559-1816.2003.tb01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Behavior and Environmental Psychology: The Role of Personal Involvement and Habit Formation in Explaining Water Consumption1

Abstract: Extending existing theory in social and environmental psychology, we develop a model to study important predictors of water consumption behavior. Overall results provide support for the predictive ability of stimuli (e.g., environmental awareness), reasoned processes (e.g., personal involvement), unreasoned processes (e.g., habits), and situational factors (e.g., income) on water consumption behavior. Findings indicate that households with lower water usage display greater awareness of water conservation issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
216
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(267 citation statements)
references
References 46 publications
29
216
5
3
Order By: Relevance
“…Other authors state that in homes with young families and with children, the average consumption is higher than in households where older people live [64,65]. It can also be observed that older people have better water saving habits, as shown in research carried out by Gregory and Di Leo [66] in Shoalhaven (Australia) and by Gilg and Barr [67] in Devon (Southwest England).…”
Section: Urban Typology and Water Consumption Trendmentioning
confidence: 49%
“…Other authors state that in homes with young families and with children, the average consumption is higher than in households where older people live [64,65]. It can also be observed that older people have better water saving habits, as shown in research carried out by Gregory and Di Leo [66] in Shoalhaven (Australia) and by Gilg and Barr [67] in Devon (Southwest England).…”
Section: Urban Typology and Water Consumption Trendmentioning
confidence: 49%
“…Although the use of a uniform distribution should seem na€ ıve, Gregory and Di Leo [2003] reported that there is little or no correlation between general awareness of water conservation issues and household consumption, but their findings substantiate the role of personal involvement and habit formation. Because of the novelty of the research on environmental psychology on the link of reasoned and unreasoned influence on behavior, we have not found any empirical-based function in the literature that could capture this personal involvement and habit formation on water savings that could perform better than the uniform distribution for the consciousness factor.…”
Section: 1002/2014wr016821mentioning
confidence: 86%
“…These assume a rational actor model, where consumers will seek to maximise the efficiency with which they meet their preferences for watering the garden (for example) given the right technology and information. However, the effectiveness of such approaches can be limited: there is a well-observed "value action gap" (Gregory and di Leo, 2003) in people's behaviour -a disjoint between reported attitudes towards the environment and actual actions to reduce water use (see, e.g. Russell and Fielding, 2010 for a review of studies), whilst household water use is typically quite inelastic to price (Arbués et al, 2003;Schleich and Hillenbrand, 2009;Arbués et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%